As mudanças climáticas no planejamento urbano de Natal/RN, Brasil: panorama, desafios e perspectivas (Revista Espinhaço, 2022)
Urban planning is crucial in tackling climate change, especially at the local level, due to key factors such as its intersectoral capacity with other agendas that are fundamental in tackling this problem (such as risk management). As the main local public policy for urban planning, the municipal master plan is an essential object of study to observe how cities and their governments are incorporating/effectively implementing the climate issue in local government agendas. In this sense, the objective of this paper is to analyze how policies and initiatives to combat climate change are incorporated into the urban planning of Natal. For that, qualitative research is used, making use of bibliographic research, documental research, participant observation and content analysis as methodological procedures. e results of this work indicate that the 2007 Natal master plan considered little, or disregarded, alignments and policies aimed at climate change. is scenario continued during its review process and took effect in March 2022 when the new city master plan bill was sanctioned by the City Hall.
Keywords: cities; local governments; adaptation; mitigation; master plan